2021
DOI: 10.1186/s12917-020-02710-y
|View full text |Cite
|
Sign up to set email alerts
|

The vaginal microflora changes in various stages of the estrous cycle of healthy female dogs and the ones with genital tract infections

Abstract: Background Inflammatory diseases of reproductive tract in bitches are a common problem in veterinary practice. The inflammation can lead to serious health problems. Research to determine the correlation between the health status of females, phase of the cycle, age and bacterial flora of the genital tract has been ongoing for years, but the results obtained by individual authors are often contradictory. Results A total of 39 dogs were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 18 publications
4
33
1
Order By: Relevance
“…Previously, microbiomes were considered as pathogens that lead to diseases [1]; however, it is now evident that they are an important part of the human and animal body, and play a crucial role in host physiology [2][3][4]. Recent advances in culture-independent DNAsequencing technology (i.e., 16S rRNA sequencing) and data analysis methods revealed that every part of a dog's body, such as the oral and nasal cavity [5,6], skin [7,8], and the gastrointestinal [9,10], respiratory [11][12][13], urinary [14], and reproductive [15][16][17] tracts, harbor certain types of microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, microbiomes were considered as pathogens that lead to diseases [1]; however, it is now evident that they are an important part of the human and animal body, and play a crucial role in host physiology [2][3][4]. Recent advances in culture-independent DNAsequencing technology (i.e., 16S rRNA sequencing) and data analysis methods revealed that every part of a dog's body, such as the oral and nasal cavity [5,6], skin [7,8], and the gastrointestinal [9,10], respiratory [11][12][13], urinary [14], and reproductive [15][16][17] tracts, harbor certain types of microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the vaginal microbiota composition fluctuates over the menstrual cycle likely due to steroid hormone-mediated changes in glycogen availability, a key nutrient source for Lactobacilli and other microbes (62,74,75). Observations in other mammals are mixed; reproductive cycle-associated fluctuations have been reported in some studies of non-human primates, bovine species, and rats (76)(77)(78)(79)(80) but not in other non-human primates, horses, or mini-pigs (81)(82)(83)(84). Like conventional C57BL/6J mice (24), we did not observe a strong influence of estrous stage on vaginal microbial compositions or individual taxa in HMb mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recognizing vaginitis is also relevant and bacterial phagocytosis is generally regarded as a hallmark of pathological conditions, such as vaginitis or pyometra (Camus et al, 2020), even if this may occur in normal animals (Groppetti et al, 2012). Bacterial flora and neutrophils also occur at diestrus (Golinska et al, 2021), which probably accounts for the misdiagnosis of diestrus in the case of vaginitis by some students. Even experienced observers, such as commercial laboratories, may incorrectly identify single smears of diestrus as proestrus and estrus as proestrus (Moxon et al, 2010), as it also occurred herein.…”
Section: Discussionmentioning
confidence: 99%